Computer aided cost estimating system / Abdul Halim Ali and Mohd Zulhairi Mohd Noor - Ali, Abdul Halim; Mohd Noor, Mohd Zulhairi (1996)
One of the most effective way of reducing industrial cost and pollution is by cutting material waste through the application of near net forming method. In the manufacturing of light engineering components, one such method is cold forging of steel where the required component shape is obtained by the application of large plastic deformation at room temperature. This result in significant cost reduction mainly by saving material compared with main alternative process, machining. The material saving is coupled with excellent surface finish and the tolerance of the component. The difficulties in the application of cold forging are associated with the strict rule which must be observed by the product designer if the process is to be economical or even applicable at all in the particular case, so forging design must be accompanied by process planning which cost estimation in product manufacture is based on a defined manufacturing process.